2022
DOI: 10.4314/tjpr.v21i5.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect and safety of combined Gegen Qinlian decoction/metformin in the treatment of diabetes mellitus in patients, and its influence on serum C peptide and glycosylated hemoglobin

Abstract: Purpose: To investigate the clinical efficacy and safety of combined Gegen Qinlian decoction /metformin in the treatment of diabetes mellitus (DM), and its influence on serum C peptide and glycosylated hemoglobin (HbAlc).Methods: One hundred and eighty-six DM patients who received treatment in Tangshan Gongren Hospital, Tangshan City, China from July 2018 to November 2019 were randomly assigned to group X (n = 93) and group Y (n = 93). Group Y was given metformin, while X received a combination of Gegen Qinlia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“… 24 Since GQD is a combination of several Chinese herbs, the effects of GQD are multi-factorial with complex mechanistic effects in T2DM, but Tu et al found that the anti-diabetic/or antihyperglycemic effects of GQD worked by regulating adipocytic PPARα and PPARγ signaling systems to maintain glucose and lipid metabolisms. 23 In this study, it was found that the combination of GQD and metformin can significantly reduce FBG, 2h PG, HbA1c levels and improve TCM syndrome, which supported the findings by Chen et al 25 …”
Section: Discussionsupporting
confidence: 88%
“… 24 Since GQD is a combination of several Chinese herbs, the effects of GQD are multi-factorial with complex mechanistic effects in T2DM, but Tu et al found that the anti-diabetic/or antihyperglycemic effects of GQD worked by regulating adipocytic PPARα and PPARγ signaling systems to maintain glucose and lipid metabolisms. 23 In this study, it was found that the combination of GQD and metformin can significantly reduce FBG, 2h PG, HbA1c levels and improve TCM syndrome, which supported the findings by Chen et al 25 …”
Section: Discussionsupporting
confidence: 88%